Computer Assisted Orthopaedic Surgery for Hip and Knee Current State of the Art in Clinical Application and Basic Research (Springer Singapore, 2018)
This book focuses on two major areas in the field of computer assisted orthopaedic surgery (CAOS): hip and knee surgery. It reviews the current clinical status of the various CAOS tools for hip and knee arthroplasty, osteotomy, ligament reconstruction, spine surgery, trauma surgery, and tumour surgery that have become available in recent years and discusses future applications based on fundamental research and continuously developing computer technology / devices. Computer Assisted Orthopaedic Surgery for Hip and Knee highlights three areas - total knee arthroplasty (TKA); total hip arthroplasty (THA) and hip osteotomy; and statistical shape modelling. It is a valuable resource for orthopaedic surgeons, clinical technologists and computer scientists and other specialists interested in this technology.